Maintaining the ability to be unsettled and learn afresh: what philosophy contributes to our understanding of 'reflection' and 'experience'. Issue 2 (4th March 2017) - Béres, Laura
Abstract: In this paper, Heidegger's and Gadamer's examinations of the terms 'reflection' and 'experience' are explored in depth in order to contribute to discussions about the benefits of critical reflection of practice for practitioners in the helping professions. The importance of maintaining humility and an undogmatic stance is stressed since this allows helping professionals to learn afresh from critical reflection of their practice. As Gadamer points out 'being experienced' does not consist of knowing everything or knowing more than anyone else. Rather, he suggests that a truly experienced person is someone who is undogmatic. This encourages practitioners to hold knowledge tentatively and be willing to be surprised by new ways of thinking and being.